平面凸轮极坐标数控加工研究 - 杨德卿; 姜小兰 (Jixie chuandong)
The NC machining of cam curves is accomplished by using common cylindrical shank milling cutter,rotary working table to control the rotary motion of planar cam and listing curves planar cam and using NC system to control linear motion and programming in polar coordinates.The centripetal and dimensional accuracy of cam curve are ensured effectively by programming in polar coordinates based on benchmark coincidence of design,clamping orientation and assembly.The machining error of cam profile is reduced effectively by using rotary coordinate control.The machining result is similar by installing a common rotary table on a common NC milling machine and using the changes of program.The application of NC technology is improved and extended by this method.